Very light magnetized jets on large scales – I. Evolution and magnetic fields - Gaibler, V.; Krause, M.; Camenzind, M. (Monthly notices of the Royal Astronomical Society, 2009)
Magnetic fields, which are undoubtedly present in extragalactic jets and responsible for the observed synchrotron radiation, can affect the morphology and dynamics of the jets and their interaction with the ambient cluster medium. We examine the jet propagation, morphology and magnetic field structure for a wide range of density contrasts, using a globally consistent setup for both the jet interaction and the magnetic field. The magnetohydrodynamic code nirvana is used to evolve the simulation, using the constrained transport method. The density contrasts are varied between η= 10−1 and 10−4 with constant sonic Mach number 6. The jets are supermagnetosonic and simulated bipolarly due to the low jet densities and their strong backflows. The helical magnetic field is largely confined to the jet, leaving the ambient medium non-magnetic. We find magnetic fields with plasma β∼ 10 already stabilize and widen the jet head. Furthermore, they are efficiently amplified by a shearing mechanism in the jet head and are strong enough to damp Kelvin–Helmholtz instabilities of the contact discontinuity. The cocoon magnetic fields are found to be stronger than expected from simple flux conservation and capable to produce smoother lobes, as found observationally. The bow shocks and jet lengths evolve self-similarly. The radio cocoon aspect ratios are generally higher for heavier jets and grow only slowly (roughly self-similar) while overpressured, but much faster when they approach pressure balance with the ambient medium. In this regime, self-similar models can no longer be applied. Bow shocks are found to be of low eccentricity for very light jets and have low Mach numbers. Cocoon turbulence and a dissolving bow shock create and excite waves and ripples in the ambient gas. Thermalization is found to be very efficient for low jet densities.